Isolation and Characterisation of a Cysteine Protease (Phytolacain G), from Phytolacca americana Roots. - Sußner, Ursula; Abel, Gudrun; Schulte, Ralf; Kreis, Wolfgang (Planta Medica, 2004)
Protein extracts obtained from dried and fresh roots of Phytolacca americana L. (Phytolaccaceae) were examined in order to identify and characterise individual proteins. The extracts were compared with a commercial pokeweed mitogen standard using SDS polyacrylamide gel electrophoresis (SDS-PAGE). A dominant protein, present in both the extracts and the pokeweed mitogen standard, was isolated by subsequent ammonium sulphate fractionation, anion exchange chromatography, gel filtration and SDS-PAGE. In this way it was purified 140-fold with about 20% yield and 70-fold with about 13% yield from dried and fresh roots, respectively. Its molecular mass as determined by gel filtration and SDS-PAGE was estimated to be about 25 kDa. Subsequent isoelectric focussing revealed one single protein band at pH 6.0. LysC digestion of the 25 kDa protein yielded several peptides which were subjected to micro-sequencing. Comparison with published sequences revealed that the protein isolated was phytolacain G, a cysteine protease previously isolated from unripe fruits of P. americana L. The enzyme showed a high affinity towards the oxidised insulin B-chain and was completely inhibited by trans-epoxysuccinyl-L-leucylamido(4- guanidino)-butane (E64). The purified phytolacain G showed "lectin- like" activities such as haemagglutination and mitogenic effects towards human lymphocytes.
UnivIS-Import:2015-03-09:Pub.2004.nat.dbio.LPB.isolat
Keywords: Cysteine protease; Phytolacain G; Phytolacca americana; Phytolaccaceae; Pokeweed mitogen